Social perspective of separate waste collection of municipal waste, a case study for a municipality in İstanbul, Turkey - GÜRSOY HAKSEVENLER, BETÜL HANDE; AKPINAR, AYDIN (My University, 2022)
IntroductionThe increasing amount of waste and the disposal process has become one of the important international problems encountered today (UNEP 2015). Worldwide rapid population growth, change in consumption habits, urbanization and economic development are the main reasons for the increase of the waste amount (Nair et al. 2021). This brings about the inadequacy of current waste management policies, while revealing the need for a sustainable and integrated waste management policy. In developed countries such as Germany, USA and Japan, significant success has been achieved by introducing new policies with the introduction of various laws and regulations regarding waste management policies (Potdar et al. 2016). However, in developing countries such as Turkey, the importance of this issue was realized later and this caused the steps taken to lag behind. For Turkey, the search for sustainable policies regarding waste management ended with the recent policy implementation of the \"Zero Waste Project\" realized under the responsibility of Turkish Ministry of Environment and Urbanization. In this concept, Zero Waste Regulation was published on 12.07.2019 in Turkey and the recycling approach became mandatory for local administrations, public institutions and organizations, industrial facilities, and etc. (MoEU 2019). With Zero Waste Management (ZWM), it is not only aimed to recycle waste, it is also aimed to eliminate or minimize the amount of waste produced by changing our consumption habits. The first step of ZWM starts with separating the wastes of individuals in their own internal environment (such as home, office). For this, it is necessary to increase the awareness of individuals by increasing the practices on a local scale and to reach the global dimension of waste recycling. Municipalities have important duties in separate waste collection (SWC) in Turkey. Studies on SWC are increasingly included in the literature as it is a current topic. However, there are limited studies on the social aspect of zero waste management. In this context, Zeytinburnu Municipality in Istanbul, Turkey which conducting a project on collecting segregated waste more efficiently was selected as a pilot study. Its separated waste collection application was analyzed by its social aspect to reveal out the knowledge, attitude, behavior, expectation and tendency of the residents. Materials and methodsIn order to evaluate the social impact of separate waste collection in Municipalities, Zeytinburnu Municipality was chosen as the pilot scale in the study since a project is carried out in the Municipality. In the project, the recyclable wastes are collected by waste collection vehicle that comes to certain neighborhoods on certain days and to fixed points. The residents receive a certain amount of payment that can be used for market shopping for the recyclable waste they bring. A survey was conducted with the residents who participate in the project in 15-30 December 2021. The number of residents who separate their waste (participate in the project) were approximately 10,000. Considering the 5% margin of error and 95% confidence interval, the sample was determined as 370 participants (RAOSOFT 2021). The questions evaluated within the scope of the study were asked to the participants on a 3-point Likert. The questions asked were aimed at evaluating the knowledge, attitude, behavior, expectation and tendency of the participants. Results and discussionIn the light of the survey results applied in the study, almost half of the residents who collect their waste separately stated that if the municipality did not have a project in this regard, they would not separate their waste. In other words, the aim of half of the residents who bring their waste in sorting the waste is the existence of an incentive mechanism such as the income obtained from the project. It was stated that around 70% of the participants had not received any information or training about SWC before, and the information obtained was provided by the municipality. To the question \"Who do you think should implement the ZWM?\", 62% of the participants answered that it should be done by the municipalities. When the participants were asked what is the main motivation in waste sorting, the answers \"basic training should be given\" and \"incentive mechanisms should be used\" were the most preferred answers (Figure 1-a). When the participants were asked what is the major challenge they face while separating waste, transporting the waste to collection/store area (45%) and having no place to separate the waste (32%) were the most given answers (Figure 1-b). (a) (b)Figure 1. How can separate waste collection practice be made more active and effective? (more than one option could be ticked) (a), What is the major challenge you face while separating waste? (b)ConclusionsUnderstanding the social dimension of waste reduction and separation significantly affects the efficiency in waste management. In the present study, the knowledge and awareness levels, motivations, and difficulties of the residents of a municipality that carries out a discrete waste collection project were determined. It is thought that the findings would give an idea not only in waste management, but also in general environmental behavior. It is also thought that these results would be a guide for decision makers and practitioners.Acknowledgements: This study is carried out by Marmara University, Urban Problems and Local Government Research and Implementation Centre and Zeytinburnu Municipality with the project supported by The Scientific and Technological Research Council of Turkey (with the number of 1919B012105189). The authors would like to thank all the municipal staff for their technical support.ReferencesMoEU, Ministry of Environment and Urbanization of Turkish Republic (2019) Regulation on Zero Waste Management (in Turkish), 30829/12.07.2019 https://www.mevzuat.gov.tr/mevzuat?MevzuatNo=32659&MevzuatTur=7&MevzuatTertip=5Nair AS, Vaiznavi B and Durga C (2021) Solid Waste and Management. Biotica Research Today 3(5): 357-359.Potdar A, Singh A, Unnnikrishnan S, Naik N, Naik M and Nimkar I (2016) Innovation in solid waste management through clean development mechanism in India and other countries. Process Safety and Environmental Protection, 101:160-169. RAOSOFT, Sample Size Calculator, 2021. http://www.raosoft.com/ samplesize.html (accessed in15.10.2021). UNEP, United Nations Environment Programme (2015) Global Waste Management Outlook United Nations. https://books.google.pl/books?id=uibGDwAAQBAJ (accessed 28 December 2021).
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Kamu Yönetimi; Kentleşme ve Çevre Sorunları; Social Sciences and Humanities; Political Science; Public Administration; Urbanization and Environmental Problems; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; KAMU YÖNETİMİ; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; PUBLIC ADMINISTRATION; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities